Measuring the Satisfaction of Students at the Completion of an Adult Learning and Development Graduate Program - Jonathon E. Messemer; Catherine A. Hansman; Elice E. Rogers (Adult Education Research Conference, 2009)
The purpose of this empirical paper is to discuss the level in which the students nearing graduation from an adult learning and development graduate program were satisfied with their learning experience. Historically, colleges and universities have been regulated by accreditation agencies, such as the North Central Association of Colleges and Schools, for the purpose of assuring that the adult learners will receive the level of education necessary to perform effectively in professional practice. Colleges of education are further regulated by agencies, such as NCATE. However, state departments of education are now requiring state institutions of higher learning to justify the need for academic programs and the level of training that is being administered in the classroom (Brand, 1997). Colleges and universities are being micromanaged from the state-level similar to the market driven model described by Kotler and Fox (1995). Faculty are now finding they are responsible for assuring the success of their educational program through numerous factors such as program enrollment, recruitment, student retention, student learning gains, and student satisfaction (Brand, 2000). Donaldson and Graham (1999) developed a model suggesting that college outcomes are dependent upon the five elements of (1) prior experience, (2) orienting frameworks (e.g., motivation, self-confidence, and values), (3) the adult’s cognition (e.g., declarative, procedural, and self-regulation of knowledge structures and processes), (4) the “connecting classroom” (e.g., avenue for social engagement and negotiating meaning for learning), and (5) the life-world environment (e.g., family, work, and community). Edwards and Usher (1997) examined the understanding of knowledge and education, the place of the university, and the responsibilities for adult educators with respect to economic, social, and cultural dimensions. A study of graduate students found that the academic programs’ level of program integration, responsiveness to change, and leadership explained 26% of the predicted value in the change of student enrollment (Milton, Watkins, Spears-Studdard, & Burch, 2003). The literature does illustrate studies that address many contextual factors between the adult learner and higher education. However, the studies do not address the degree to which the academic program is meeting the needs of the adult learners and the demands from governing accreditation agencies, state departments of education, and the administrators of higher education. The purpose of this study was to understand the level to which our graduate students were satisfied with their learning experience while pursuing a master’s degree in adult learning and development.